Evaluation of pharmaceutical services, the level of satisfaction and waiting time at Betung City Primary Health Care, Banyuasin Regency - Reza Agung Sriwijaya (Universitas Islam Indonesia, 2022)
Background: Pharmaceutical services play an important role in the success of patient treatment in health centers, therefore it is necessary to evaluate the management of pharmaceutical preparations and clinical pharmacy services and see the level of patient satisfaction and waiting time for prescriptions in health centers by comparing those stipulated in the regulation of the minister of health no 74 of 2016 and no 129 year 2008Objective: The purpose of this study was to evaluate the management of Consumable Medical Materials (BMHP) services, clinical pharmacy services based on Minister of Health Regulation No. 74 /2016 and Permenkes no 129/2008.Methods : This research is an observational, experimental, quantitative descriptive, cross-sectional study with prospective data collection, survey methods and interviews. Measuring instrument research, questionnaire sheet, which has been validated. Inclusion criteria are pharmacy staff who are responsible for pharmacy services at Betung Public Health Center, Banyuasin Regency. The data obtained in the form of qualitative and quantitative descriptive data.Result : The results of the study obtained services according to Permenkes No. 74 of 2016 management of pharmaceutical preparations and medical consumables of 88.26% (good) and clinical pharmacy services 26.2% (less) especially in Drug Information Services (PIO), Monitoring of Side Effects Drugs (MESO), and Drug Therapy Monitoring (PTO), the visits have not been carried out, patients are very satisfied with the services of the Betung Health Center and the average waiting time for prescription services is 4 minutes 13 seconds according to the Regulation of the Minister of Health No. 129 Year 2008.Conclusion : Pharmaceutical services that are in accordance with Permenkes No.74 of 2016 on the management of pharmaceutical preparations and BMHP are in accordance with 88.26% but clinical pharmacy services are not in accordance with Permenkes 74/2016 by 21.3% (less category), especially in clinical pharmacy services which What has not been implemented is drug information service (PIO) by 33.05% and what has not been implemented, namely monitoring of drug side effects (MESO) and monitoring of drug therapy (PTO), Visit by 0%. The level of patient satisfaction is very satisfied with the puskesmas services with a percentage of 81.3% seen from the 5 dimensions, the average value of waiting time for prescription services is 4 minutes 13 seconds according to the Ministry of Health no. 129 in 2008.Keywords: puskesmas, pharmaceutical services, Permenkes IntisariLatar belakang: Pelayanan kefarmasian memegang peranan penting dalam keberhasilan pengobatan pasien di puskesmas. Dengan demikian, perlu dilakukan evaluasi pada pengelolaan sediaan farmasi dan pelayanan farmasi klinik serta melihat tingkat kepuasan pasien dan waktu tunggu resep di Puskesmas.Tujuan: Penelitian ini bertujuan untuk mengevaluasi pengelolaan pelayanan Bahan Medis Habis Pakai (BMHP), pelayanan farmasi klinik berdasarkan Peraturan Menteri Kesehatan (Permenkes) No. 74/2016 dan Keputusan Menteri Kesehatan (Kepmenkes) nomor 129/2008.Metode: Rancangan penelitian ini adalah potong lintang dengan metode survei dan observasional. Pengumpulan data secara prospektif, dengan pembagian kuesioner yang telah valid dan wawancara. Jumlah responden adalah 80 pasien dan satu tenaga kefarmasian yang bertanggung jawab atas pelayanan kefarmasian di Puskesmas Betung Kabupaten Banyuasin. Data yang diperoleh dianalisis secara deskriptif.Hasil: Hasil penelitian menunjukkan pengelolaan sediaan farmasi dan BMHP di sebesar 88,26% (kategori baik) dan pelayanan farmasi klinik 26,2% (kategori kurang) khususnya kegiatan Pelayanan Informasi Obat (PIO), Monitoring Efek Samping Obat (MESO), dan Pemantauan Terapi Obat (PTO), visite belum dilakukan. Pasiensangat puas (81,3%) terhadap pelayanan Puskesmas Betung dan rata-rata waktu tunggu pelayanan resep adalah 4 menit 13 detik sesuai Kepmenkes No. 129/2008.Kesimpulan: Pelayanan kefarmasian yang telah sesuai dengan Permenkes No.74 Tahun 2016 yaitu tentang Pengelolaan Sediaan Farmasi dan BMHP, sedangkan pelayanan farmasi klinik belum sesuai. Sebagian besar telah merasa puas terhadap pelayanan kefarmasian di Puskemas Betung dan waktu tunggu telah sesuai dengan persyaratan.Kata kunci: puskesmas, pelayanan kefarmasian, waktu tunggu, kepuasan